2019
DOI: 10.1038/s41467-019-10152-w
|View full text |Cite
|
Sign up to set email alerts
|

Aβ34 is a BACE1-derived degradation intermediate associated with amyloid clearance and Alzheimer’s disease progression

Abstract: The beta-site APP cleaving enzyme 1 (BACE1) is known primarily for its initial cleavage of the amyloid precursor protein (APP), which ultimately leads to the generation of Aβ peptides. Here, we provide evidence that altered BACE1 levels and activity impact the degradation of Aβ40 and Aβ42 into a common Aβ34 intermediate. Using human cerebrospinal fluid (CSF) samples from the Amsterdam Dementia Cohort, we show that Aβ34 is elevated in individuals with mild cognitive impairment who later progressed to dementia. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
48
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 51 publications
(54 citation statements)
references
References 68 publications
5
48
0
1
Order By: Relevance
“…Furthermore, a recent study found a correlation between Aβ peptide length and plaque load (Aβ 1-43 > Aβ 1-42 > Aβ 1-40 ), indicating that longer Aβ peptides have an increased tendency towards accumulation in the brain [23], thus explaining their lower CSF levels. Further analysis of the shorter Aβ species Aβ 1-41 , Aβ 1-37 (from Aβ 1-43 ) Aβ 1-38 (from Aβ 1-42 ) and Aβ 1-34 (from either Aβ 1-43 or Aβ 1-42 ) are however needed to better clarify the role of longer Aβ peptides in AD and the pathogenic events linked to Aβ process, degradation and clearance in the presence of APP and PSENs mutations [9][10][11].…”
Section: Mutation Screeningmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, a recent study found a correlation between Aβ peptide length and plaque load (Aβ 1-43 > Aβ 1-42 > Aβ 1-40 ), indicating that longer Aβ peptides have an increased tendency towards accumulation in the brain [23], thus explaining their lower CSF levels. Further analysis of the shorter Aβ species Aβ 1-41 , Aβ 1-37 (from Aβ 1-43 ) Aβ 1-38 (from Aβ 1-42 ) and Aβ 1-34 (from either Aβ 1-43 or Aβ 1-42 ) are however needed to better clarify the role of longer Aβ peptides in AD and the pathogenic events linked to Aβ process, degradation and clearance in the presence of APP and PSENs mutations [9][10][11].…”
Section: Mutation Screeningmentioning
confidence: 99%
“…The latter undergoes additional cleavages by γ-secretase to generate a series of Aβ peptides 39-43 amino acids long, following two different pathways: Aβ 1-49 > Aβ 1-46 > Aβ 1-43 > Aβ 1-40 and Aβ 1-48 > Aβ 1-45 > Aβ 1-42 > Aβ 1-38 [8]. Shorter peptides can also be produced, including Aβ 1-41 from Aβ 1-43 [9] and Aβ 1-34 from either Aβ 1-42 or Aβ 1-40 [10], which is considered a biomarker of Aβ clearance and AD progression [11]. Pathogenic mutations in APP and PSEN1 and 2 (γ-secretase's catalytic subunits) are known to influence APP metabolism leading to the deposition of Aβ peptides.…”
Section: Introductionmentioning
confidence: 99%
“…This additional BACE1 mediated cleavage can only take place with Aβ peptides as substrates implying that BACE1 indeed acts as an Aβ40/42 degrading enzyme to generate Aβ34 [19, 50]. In a recent study, we were able to show that Aβ34 levels are directly affected by over-expression or inhibition of BACE1 both in vitro and in vivo, and that cerebral BACE1 is the critical factor for Aβ34 generation [30]. Supporting its proposed role as a biomarker for clearance in sporadic AD, CSF Aβ34 levels were found to be elevated in subjects with mild cognitive impairment (MCI) who later converted to AD dementia [30].…”
Section: Introductionmentioning
confidence: 99%
“…In a recent study, we were able to show that Aβ34 levels are directly affected by over-expression or inhibition of BACE1 both in vitro and in vivo, and that cerebral BACE1 is the critical factor for Aβ34 generation [30]. Supporting its proposed role as a biomarker for clearance in sporadic AD, CSF Aβ34 levels were found to be elevated in subjects with mild cognitive impairment (MCI) who later converted to AD dementia [30]. Moreover, we also discovered a positive correlation between CSF Aβ34 levels and overall Aβ clearance rates in individuals with biomarker evidence of cerebral amyloid deposition [30].…”
Section: Introductionmentioning
confidence: 99%
“…However, a causal effect between β’-cleavage and neuroprotection is not straight forward as Aβ 11–40 is found in insoluble Aβ pools of post-mortem AD brains (Huse et al, 2002). More recently, it has been shown that BACE-1 can also cleave Aβ 40 or Aβ 42 to generate a C-terminal truncated Aβ 34 form, which appears to be a new biomarker of Aβ clearance in AD as it is noticeably increased in mild cognitive impaired patients along with strong BACE-1 activity (Liebsch et al, 2019). Together, these data confirm early studies (Fluhrer et al, 2003; Shi et al, 2003), placing BACE-1 as a prominent Aβ-generating, but also as an occasional Aβ-“degrading” enzyme under some circumstances.…”
Section: Alzheimer’s Disease a Proteolytic Problemmentioning
confidence: 99%